Factors Correlated with Postoperative Hospital Stay after Prophylactic Use of Metronidazole during Major Gynaecological Operation - Khatun, Mahmuda; Sultana, Rifat; Banu, Dewan Sahida; Ashraf, Rumana; Sultana, Nasrin; Aktar, Mst Nurun Nahar; Mondal, Dipika Rani (Journal of Science Foundation, 2018)
Background: Prophylactic use of metronidazole prevents infection among the women undergone major gynaecological operations. Objectives: The purpose of the present study was to correlate post operative hospital stay with age, weight and duration of operation among the women with prophylactic use of metronidazole during the major gynaecological operation. Methodology: This comparative cross-sectional study was conducted in the Department of Obstetrics and Gynaecology at Bangabandhu Sheikh Mujib Medical University, Dhaka from August 2002 to January 2003 for a period of six (6) months. All the women who were undergone major gynaecological operation at any age were selected as study population. Minor gynaecological operation cases were excluded from this study. The data were collected by face to face interview. The age, weight and duration of operation as well as type of operation were recorded. Result: The mean ± SD postoperative hospital stay for wound healing of group A and B patients were 8.24±2.44 (range 5 to 17) and 8.83±3.21 (range 5 to 20) days, respectively (p=0.226). It shows a positive correlation that is increasing age is significantly related (P<0.00l) to increase in hospital stay for wound healing in both group A and B patients. The correlation between weights of the patients with postoperative hospital stay for wound healing shows a positive correlation, that is, increasing weight is significantly related to increase in hospital stay for wound healing in both group A and B patients (p=0.0001). Conclusion: In conclusion age and weight of the patients as well as the duration of operation is positively correlated with the wound healing among the women who are under metronidazole prophylactic therapy. Journal of Science Foundation 2017;15(1):3-8